Analisis Kasus Penistaan Agama oleh Panji Gumilang (Ponpes Al-Zaytun) Dalam Prespektif Hukum dan Masyarakat - Sifana, Firdha; Lewoleba, Kayus K (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Blasphemy in Indonesia is a criminal offense that is considered a serious and sensitive matter if it occurs in the midst of society, especially in the world of education such as boarding schools. Panji Gumilang in his position as leader of Al-Zaytun boarding school in Indramayu committed blasphemy or blasphemy verbally or in other ways. The research method used in this research is normative legal research method. The result of this research is that Panji Gumilang was determined as a suspect in a blasphemy case based on his actions in the form of spreading deviant Islamic teachings to santri and santriwati of Al-Zaytun Islamic boarding school and his statements which are also deviant regarding the understanding of Islamic teachings. The government has made every effort in addressing this case by naming Panji Gumilang as a suspect as a form of maintaining religious harmony in Indonesia, besides that the government also guarantees the educational rights of the students and santriwati ponpes Al-Zaytun, the government through KEMENAG also provides guidance and guidance for teachers and education personnel ponpes Al-Zaytun as an effort to overcome the deviation of Islamic teachings in the education system ponpoes Al-Zaytun.